Leaf reference values for ‘Pérola’ pineapple quality using compositional nutrient diagnosis - Belarmino Rodrigues, João Batista; da Silva, Alexandre Paiva; Rozane, Danilo Eduardo [UNESP]; Natale, William; de Melo Silva, Silvanda (Taylor & Francis, 2021)
The leaf reference values for pineapple available in the literature were obtained using bivariate methods that aim to reach maximum yield; however, plant nutrition also influences the fruit quality. This study aimed to generate reference values for the ‘Pérola’ pineapple grown in the Paraíba State using compositional nutrient diagnosis (CND) in order to maximize fruit yield and quality. The study used data of fruit weight, soluble solids (SS), titratable acidity (TA), SS/TA ratio, and leaf concentrations of N, P, K, S, Ca, Mg, Cu, Fe, Zn, Mn, and B of the pineapple cultivar ‘Pérola’ originated from fertilization trials. The treatments consisted of the combination of two matrices: the modified Pan Puebla III matrix and the Baconian matrix, which assessed the variation in the levels of N, P, K, and S and the variation in the levels of liming and micronutrients, respectively, totaling 30 treatments in a randomized block design with 90 plots and three replications per experiment. The CND method was used to obtain reference values. There were differences in the mean nutrient concentrations between the high and low-quality populations; however, there was no difference between the nutrient concentrations that promoted the highest fruit weight and those that promoted the highest quality index. The sufficiency ranges for ‘Pérola’ pineapple obtained by CND methodology aiming at the quality index and yield were: N:10.9–14.2; P:1.2–1.6; K: 35.6–42.8; S: 1.0–1.5; Ca: 2.3–3.7; Mg: 1.5–2.2 g kg−1; Cu: 1.1–3.1; Fe: 30.4–52.6; Zn: 4.0–8.5; Mn: 129.2–175.9; and B: 18.8–27.4 mg kg−1.
Keywords: Ananas comosus comosus; CND norms; critical levels; sufficiency ranges